Purposeful and Ethical Early Childhood Teacher: The Underlying Values Guiding Finnish Early Childhood Education - Melasalmi Anitta; Hurme Tarja-Riitta; Ruokonen Inkeri (Sage Publications Ltd., 2022)
Purpose: The new Finnish National Core Curriculum for Early Childhood Education and Care (2018) strongly highlights pedagogical knowledge and practice, demanding teachers to develop their pedagogical thinking, evaluation, judgment, and operating culture. Since ethics is viewed as vital characteristics of the teaching profession, our objective is to make these complex ethical issues more visible to be subject to democratic discussion and change.
Design/Approach/Methods: The framework comprises a broad theory base of codes of ethics and professional codes of ethics of teaching. The research materials were national curricula of early childhood education and care (ECEC)- and preprimary education. The eight-step qualitative analysis process was applied to identify and shed light on the codes of ethics laying the foundations for purposeful and ethical early childhood education (ECE) teacher.
Findings: The results indicate that through both theoretical lenses, the Finnish ECEC curricula comprise several ethical codes. For the future purposeful ECE teachers as ethical professionals, the results raise questions for further discussion. Particularly, issues related to the ethics of care, intellectual freedom, inquiry stance, and professional competence, and diversity may further enhance our ECEC curricula.
Originality/Value: During recent decades, the ethics concerning ECEC have gained increasing global attention. Particularly, there is a large international consensus considering ECEC as a prominent policy equalizing opportunities.